Internalization of Staphylococcus aureus by Human Keratinocytes - Kintarak, Sompid (American Society for Microbiology, 2004)
Staphylococcus aureus is among the most important human pathogens and causes various superficial and systemic infections. The ability of S. aureus to be internalized by, and survive within, host cells, such as keratinocytes, may contribute to the development of persistent or chronic infections and may finally lead to deeper tissue infections or dissemination. To examine the mechanisms of internalization of S. aureus by keratinocytes, isogenic mutants lacking fibronectin-binding proteins (FnBPs), a recombinant protein consisting of the fibronectin-binding domain of S. aureus FnBPs, and an anti-α5β1 antibody were used in cocultures with immortalized keratinocytes and primary keratinocytes. We found that internalization of S. aureus by immortalized keratinocytes requires bacterial FnBPs and is mediated by the major fibronectin-binding integrin α5β1. In contrast to internalization by immortalized keratinocytes, internalization of S. aureus by primary keratinocytes could occur through FnBP-dependent and -independent pathways. S. aureus clumping factor B (ClfB), which was recently determined to bind to epithelial cells, was not involved in the uptake of this bacterium by keratinocytes. The identification of an alternate uptake pathway, which is independent of S. aureus FnBPs and host cell α5β1, has important implications for the design of therapies targeted to bacterial uptake by host cells.